ʿIṣmat Cuġtāʾī ke afsānoṉ kā tanqīdī mut̤ālaʿah - Jabīṉ, S̱uraiyā (Ṣāʾimah Pablīkešanz, 2016)
Critical study on the fictional works of ʿIṣmat Cug̱ẖtāʾī, 1915-1991, Urdu litterateur
Includes bibliographical references (pages 109-112)
Keywords: Cug̱ẖtāʾī; ʿIṣmat 1915-1991